The Antibiotic Resistance Patterns of Klebsiella pneumoniae Clinic Isolates: A Comprehensive Meta-Analysis - Elmas Pınar Kahraman; İhsan Hakkı Çiftci (Open Journal of Bacteriology - Peertechz Publications, 2017)
Background/Purpose: Recently, Klebsiella pneumoniae has become a health care concern due to its production of extended-spectrum beta-lactamase (ESBL) and its resistance to carbapenem. In Turkey, systematic meta-analyses investigating antibiotic resistance in K. pneumoniae are lacking. Methods: Consequently, we performed a systematic review of the literature followed by a metaanalysis to investigate antibiotic resistance in K. pneumoniae. This study was designed and conducted in accordance with the PRISMA guidelines. We identified observational studies published from 2000 to 2015 using the various search engines. In total, 2,225 articles were published during this study period, but we only included 25 in our meta-analysis because of eligibility criteria. Results: We observed a significant increase in antibiotic resistance (>40%) to the following antibiotics: cefazolin, amoxicillin-clavulanic acid, cefuroxime, cefepime, ceftriaxone, and ceftazidime. Unfortunately, the majority of these antibiotics were commonly prescribed for the treatment of K. pneumoniae infections. The rate of bacterial ESBL production has been steadily increasing and in this study was calculated at 39.66% ± 12.46%. In this study, we observed >30% resistance to ciprofloxacin. Furthermore, the rates of resistance to imipenem and meropenem were 5.1% and 3.4%, respectively. Conclusion: The data obtained from this study may be beneficial for prescribing appropriate antibiotics and preventing their unnecessary use. The frequent checks of resistance rates with new detailed report may suggest to the development of National Antibiotic Stewardship.